Biomechanics of Heading a Soccer Ball: Implications for Player Safety - Charles F. Babbs (The Scientific World Journal)
To better understand the risk and safety of heading a soccer ball, the author created a set of simple mathematical models based upon Newtons second law of motion to describe the physics of heading. These models describe the player, the ball, the flight of the ball before impact, the motion of the head and ball during impact, and the effects of all of these upon the intensity and the duration of acceleration of the head. The calculated head accelerations were compared to those during presumably safe daily activities of jumping, dancing, and head nodding and also were related to established criteria for serious head injury from the motor vehicle crash literature. The results suggest heading is usually safe but occasionally dangerous, depending on key characteristics of both the player and the ball. Safety is greatly improved when players head the ball with greater effective body mass, which is determined by a players size, strength, and technique. Smaller youth players, because of their lesser body mass, are more at risk of potentially dangerous headers than are adults, even when using current youth size balls. Lower ball inflation pressure reduces risk of dangerous head accelerations. Lower pressure balls also have greater “touch” and “playability”, measured in terms of contact time and contact area between foot and ball during a kick. Focus on teaching proper technique, the re-design of age-appropriate balls for young players with reduced weight and inflation pressure, and avoidance of head contact with fast, rising balls kicked at close range can substantially reduce risk of subtle brain injury in players who head soccer balls.